PELATIHAN MENGANALISIS BUTIR SOAL DENGAN MENGGUNAKAN APLIKASI ITEMAN PADA MAHASISWA PGSD SMESTER VI INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Taufik, Ahmad; Ashari, Lalu Hasan; Vandita, Lalu Yoga; Wahyudi, Johan; Syahrial, Feri (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
The assessment process does not end with just asking questions. They will come to an analysis of the quality of the questions. Item analysis was carried out to determine the quality of the items prepared. Questions that are of good quality will greatly affect the results of the assessment and capture the learning outcomes well. The purpose of this training is to introduce how to analyze items using ITEMAN by paying attention to the characteristics of the level of difficulty, discriminating power, and the function of the item distractor. This research is descriptive research using observation, interview, and evaluation methods. Participants in this training consisted of 25 students and female students who were students from IPNG. The results of this study were that all participants felt helped in making questions that would soon set their feet in the world of education and some of them even became teachers or instructors. This means that the ITEMAN application really helps our teachers to compose questions.